Respostas

A melhor resposta!
2013-04-02T17:31:26-03:00

é só substituir o x pelos números que estão entre parenteses.

 

A- f(0)

f(0)= 3.0 + 7

f(x)= 7

 

B- f(1)

f(1)= 3.1 + 7

f(1)= 10

 

C- f(2)

f(2)= 3.2 + 7

f(2) = 13

 

D- f(3)

f(3)= 3.3 + 7

f(3)= 16

 

E- f(-1)

f(-1)= 3.(-1) + 7

f(-1)= 4

 

F- f(5)

f(5)= 3.5 + 7

f(5)= 22

1 5 1
2013-04-02T17:33:11-03:00

f(x)=3.0+7

  f(x)=0+7

f(x)=7

 

b)f(x)=3.1+7

f(x)=10

 

c)f(x)=3.2+7

f(x)=13

 

d)f(x)=3.3+7

f(x)=16

 

e)f(x)=3.(-1)+7

f(x)=4

 

f)f(x)=3.5+7

f(x)=22

1 5 1